Anxiety and Depression in Chinese Students During the COVID-19 Pandemic: A Meta-Analysis - Zhang, Yaoyao; Bao, Xiuqin; Yan, Jiaxin; Miao, Hualing; Guo, Cheng (Frontiers in Public Health, 2021)
Background: The novel 2019 coronavirus disease (COVID-19) pandemic has spread rapidly worldwide and poses a global health threat. Aims: This study aimed to assess the prevalence of anxiety and depression symptoms in Chinese students during the COVID-19 pandemic as well as to explore potential moderating factors. Methods: We searched English and Chinese databases using pertinent keywords for articles published and unpublished, up until November 2020. The estimate of the overall prevalence of anxiety and depression was conducted through a random-effects model. Results: A total of thirty-one cross-sectional studies were included. The overall prevalence of anxiety and depression symptoms in Chinese students during the COVID-19 pandemic was 24.0% (95% CI [20.0–29.0%]) and 22.0% (95% CI [18.0%–27.0%]) respectively. Subgroup analyses revealed that Chinese middle school students were at a heightened risk of anxiety, while university students were at a heightened risk of depression. Students who live in higher-risk areas appeared severe anxiety and depression, especially during the late period of the COVID-19. Conclusions: Overall, the COVID-19 pandemic is related to the high level of anxiety and the medium level of depression in Chinese students. Therefore, comprehensive and targeted psychological interventions should be developed to address the mental health of students at different study grades, especially in high-risk areas and during the late period of the COVID-19 pandemic.